Insurance regulations, risk and performance in Ghana - Kusi, B.A.; Alhassan, A.L.; Ofori-Sasu, D.; Sai, R. (Journal of Financial Regulation and Compliance, 2019)
Purpose – This study aims to examine the hypothesis that the effect of insurer risks on profitability is conditional on regulation, using two main regulatory directives in the Ghanaian insurance market as a case study. Design/methodology/approach – This study used the robust ordinary least square and random effect techniques in a panel data of 30 insurers from 2009 to 2015 to test the research hypothesis. Findings – The results suggest that regulations on no credit premium and required capital have insignificant effects on profitability of insurers. On the contrary, this study documents evidence that both policies mitigate the effect of underwriting risk on profitability and suggests that regulations significantly mitigate the negative effect of underwriting risk to improve profitability. Practical implications – The finding suggests that policymakers and regulators must continue to initiate, design and model regulations such that they help tame risk to improve the performance of insurers in Ghana. Originality/value – This study provides first-time evidence on the role of regulations in controlling risks in a developing insurance market.
Research Article
Keywords: Regulations; Liquidity risk; Insurers’ performance; Underwriting risk